Eye-Drops for Activation of DREADDs - Keenan, William T.; Fernandez, Diego C.; Shumway, Lukas J.; Zhao, Haiqing; Hattar, Samer (Frontiers in Neural Circuits, 2017)
Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) are an important tool for modulating and understanding neural circuits. Depending on the DREADD system used, DREADD-targeted neurons can be activated or repressed in vivo following a dose of the DREADD agonist clozapine-N-oxide (CNO). Because DREADD experiments often involve behavioral assays, the method of CNO delivery is important. Currently, the most common delivery method is intraperitoneal (IP) injection. IP injection is both a fast and reliable technique, but it is painful and stressful particularly when many injections are required. We sought an alternative CNO delivery paradigm, which would retain the speed and reliability of IP injections without being as invasive. Here, we show that CNO can be effectively delivered topically via eye-drops. Eye-drops robustly activated DREADD-expressing neurons in the brain and peripheral tissues and does so at the same dosages as IP injection. Eye-drops provide an easier, less invasive and less stressful method for activating DREADDs in vivo.